FV4. Comparing whole-brain susceptibility patterns in patients with Alzheimers disease and cerebral amyloid angiopathy: A QSM study. Issue 8 (August 2018) - Perosa, V.; Schreiber, S.; Düzel, E.; Assmann, A.; Bittner, D.; Schreiber, F.; Acosta-Cabronero, J.
Abstract : Background: Evidence exists, that cerebral amyloid angiopathy (CAA) and Alzheimer's disease (AD) partially share pathophysiological pathways, including the accumulation of amyloid in the vessels' walls and vascular damage (Charidimou et al., 2017). Further hints are the similar distribution of Amyloid b in PET studies (Johnson et al., 2007) and the presence of microbleeds in both AD and CAA (Cordonnier and Flier, 2011). Iron accumulation has been proposed as a marker of neural degeneration (Ward et al., 2014) and its global distribution can be assessed in vivo using quantitative susceptibility mapping (QSM) in magnetic resonance imaging (MRI) (Acosta-Cabronero et al., 2017). Using QSM, we aim to compare the magnetostatic distribution patterns of CAA and AD patients. Methods: 25 patients affected by CAA, 25 AD patients and 25 community-dwelling elderly adults underwent high-resolution MRI at 3T (1.0 × 1.0 × 2.0 mm). After QSM reconstruction, whole brain analysis, will be performed using FSL (Jenkinson et al., 2012) to compare susceptibility maps between groups. Sex, age and educational level will be set as nuisance variables, while clusters will be considered significant when p (FEW) < 0.05. We additionally plan a regression analysis to investigate correlation between QSM distribution pattern and cognitive measures (i.e. MMSE). Regional QSM values of cortical (i.e. occipital cortex) and subcortical (basal ganglia and hippocampus) regions of interest will further be analyzed. Hypothesis: We expect to observe partially overlapping patterns in the magnetostatic distribution of CAA and AD patients, and additionally suppose to find group differences, such as the prevalence of occipital iron accumulation in CAA patients. In this case, a disease specific QSM-pattern could be suggested as a complementary diagnostic tool. Results will be available before end of the year.